PENGARUH INTERNET FINANCIAL REPORTINGTERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016-2020 - Fatmaniar Hepy Putri Ramadhanty; Diana Zuhroh; Sutini (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
The role of internet financial reporting is increasingly needed. Internet financial reporting is believed to be able to contribute to increasing the value of the company. This study aims to examine the effect of internet financial reporting on firm value.This type of research is an empirical study. The population in this study are all companies listed on the Indonesia Stock Exchange and publishing financial statements in a row for the 2016-2020 period. The number of samples obtained as many as 47 companies were selected as the number of representative samples. This study uses observational data for one period. The data analysis technique used simple linear regression.The results show that internet financial reporting has an effect on the value of the company as measured by the value of Tobin's Q.